Extraction and identification of essential oil components from the leaves of Syzygium malaccense (L.) MERR. & L.M. PERRY, MYRTACEAE - Feltrin, Fabiula Marta; Gibbert, Luciana; Santos, Nayana Cristina da Silva; Marques, Francisco de Assis; Miguel, Marilis Dallarmi; Zanin, Sandra Maria Warumby; Miguel, Obdúlio Gomes; Krüger, Cláudia Carneiro Hecke; Dias, Josiane de Fátima Gaspari (Ciência e Natura, 2022)
Popularly known as red jamb, the species Syzygium malaccense (L.) Merr. & L.M. Perry is an Asian tree from India, Malaysia, Vietnam and Thailand that has adapted to the climate and soil of the North, Northeast and Southeast of Brazil. The antioxidant and anti-inflammatory activities of this species have already been cited in the literature. This study aimed to extract and identify the essential oil constituents of the leaves of this species. The leaves were dried and ground; and the essential oil was extracted by Clevenger apparatus. The essential oil presented yield of 0.03%, containing monoterpenes and sesquiterpenes and the major compounds were identified as spatulenol, sesquisabinene transhydrate and (E) -Caryophyllene.